Improved functional outcome in patients with early rheumatoid arthritis treated with intramuscular gold: results of a five year prospective study. Issue 2 (1st February 1998) - Munro, Robin; Hampson, Rosie; McEntegart, Anne; Thomson, E Anne; Madhok, Rajan; Capell, Hilary
Abstract : OBJECTIVE: To determine whether there is a relation between disease duration and functional outcome in patients with rheumatoid arthritis (RA) treated with intramuscular sodium aurothiomolate (gold) for five years. METHODS: 440 patients with RA were enrolled in a prospective trial of gold treatment. Initial demographic details were recorded. Disease activity was assessed at yearly intervals using a combination of clinical (pain score, Ritchie articular index, duration of morning stiffness) and laboratory (erythrocyte sedimentation rate, C reactive protein) parameters. Change in functional status was assessed using the health status questionnaire (HAQ). Patients were stratified according to disease duration at outset (group 1= 0–2 years n=106, group 2 = >2–5 years n=93, and group 3= >5 years n=235). RESULTS: There were no significant differences between the groups at outset. A total of 160 patients completed five years of treatment (group 1 n=44 (42%), group 2 n=37 (40%), and group 3 n=79 (34%)). Patients in group 1 had a significantly lower HAQ from year 1 to year 5 with a mean improvement of 30% at the end of the study (p<0.001). Neither group 2 nor group 3 had a significant change in their HAQ at study end. There were significant improvements in all other variables (p<0.05) in each group apart from pain in group 2. CONCLUSION: Patients with early RA have a larger reversible component to their HAQ. Only patients with disease duration of up to two years have a longlasting improvement in their functional ability after starting intramuscular gold treatment.